Food writings in a postmodern society: a discourse analysis of influencer and celebrity chef cookbooks in Belgium - Proesmans, Viktor L. J.; Vermeir, Iris; Teughels, Nelleke; Geuens, Maggie (Frontiers in Communication, 2023)
Abstract Food writings are changing tremendously over the years. Traditional cookbooks with an informational purpose have mostly been replaced by more hybrid edutaining cookbooks authored by celebrity chefs and influencers. To get a better grasp on this evolution, we conducted a critical discourse analysis on 18 of the best-selling cookbooks in Flanders (Belgium) published in 2008-2018. Using the three-dimensional framework of Fairclough, we analyze what cookbooks proclaim, how the discourse evolved over time, and how it relates to society. Our findings show that modern cookbooks, beside their informational purpose, aim to inspire and entertain using a personal discourse focused on shared values and authenticity. Celebrity chefs, for example, emphasize tradition, family, and the fun of cooking, whereas influencers provide life advice focusing on postmodern values like moral choice, achievement, fulfillment, and personal responsibility. Influencers also take an anti-establishment position villainizing “conventional science” and processed food, acting on the increasing societal distrust towards food science and the food industry.